Prevalence and therapeutical Study of Gastrointestinal Nematodes in Local Goats in Northern of Iraq - Alaa Kamil Mahmood; Zeyad Taha Hussein; Omar-Althani S. Saed; Maher S. Owain (Institute of Medico-legal Publications Pvt Ltd, 2021)
The purpose of this study was to study the species and prevalence GINs and detect the efficacy and resistanceof some anthelmintics in local goats in northern Iraq. A total of 180 local goats originating from 25 goatfarms were examined. As a result twelve species of these worms have been diagnosed, with a percentageof infection 64.44%, The Marshallagia spp. had the highest incidence 53.4%. The efficacy of anthelminticdrugs in the 3rd week after treatment for each the Ivermectin, A sativum, C colocynthis and O oil, reached to95.3, 62.3, 92 and 31.2% respectively, and the study noted that there is resistance to some of these therapiesby some types of worms.